Perbedaan Tingkat Kecemasan Antara Siswa Sekolah Dasar Terhadap Pemeriksaan Gigi dan Mulut - Lesmana, Hans; Sitanaya, Rini; Irayani, Surya; Nurilmi (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2023)
Anxiety is the biggest obstacle for Dentists in carrying out optimal treatment. Anxiety in children is a problem that causes children to delay or refuse dental treatment. Delays in dental treatment can cause the patient's oral health level to get worse and increase the child's fear of going to the dentist. The group of elementary school children (age 6-12 years) is a group that often experiences dental and oral health problems, so they need vigilance and proper dental care. This study aims to determine differences in the level of anxiety of grades 3 and 6 regarding dental and oral examinations at SDN Minasa Upa. The type of research used is Analytical Observational with a cross-sectional design. The sample in this study amounted to 66 samples, 33 class 3 samples and 33 class 6 samples with a sampling technique called is Simple Random Sampling. Data analysis was performed using the Mann Whitney test to examine the differences between the two groups of respondents. Statistical test results with the Mann Whitney test in grade 3 students and the class scored Asymp. Sig 0.000 (<0.05). These results indicate that there are differences in the level of anxiety between grade 3 and grade 6 students regarding dental and oral examinations at SDN Minasa Upa. Where the level of class anxiety tends to be more anxious than grade 6 students about dental examinations. Keywords: Child anxiety; anxiety level; dental check